ERRORS MADE BY STUDENTS OF UNIVERSITAS KHAIRUN IN SIMPLE PAST TENSE - Misna Rusli; Indry Widyasti Anwar; Susana R. Bahara (Jurnal Bilingual, 2024)
The aim of this study is to identify errors in the usage of the simple past Tense in the written work of second-semester Class A students in the English education program at Khairun University. The study included 27 students as subjects, and data was collected through written tests and interviews. The researcher utilized Dulay's Theory to categorize the types of errors, finding three main types: omission, addition, and misformation. The frequency of errors was as follows: omission (2.5%), addition (0.75%), and misformation (67.5%). Misformation emerged as the most prevalent error type. Based on interview results, the most common causes of simple past tense errors were students' need for understanding of grammar and simple past tense formulas, as well as a limited vocabulary leading to difficulty in constructing sentences. Additionally, students needed help with the placement of past tense verbs in sentences. These errors were further made worse by inadequate study time, overreliance on in-class learning, and less allocated self-study time at home.